2017
DOI: 10.4274/uob.857
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sex and Age Differences on Pathology Results in Primary Bladder Cancer Patients

Abstract: Objective: Bladder cancer is more frequently seen in males, whereas prognosis is usually worse in female patients. Although many factors affect the prognosis of urothelial carcinoma of bladder have been proposed, the effect of female gender on the prognosis of bladder urothelial carcinoma is controversial. Several factors have been suggested regarding the effect of gender difference on the prognosis of bladder urothelial carcinoma. Materials and Methods: A retrospective study of 589 patients who underwent tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
1
1
1
Order By: Relevance
“…Bladder malignancy is further frequently noted among males, while prognosis is generally worse among females. 13 In this study males were found in the majority 51(61.4%) and females were 32(38.6%), which is similar to the study of Türk H et al, 13 which reported that out of five hundred sixty-nine patients, 497 (87.30%) cases were males and 72 (12.70%) were females. In recent times, many reviews have summarized and interpreted outcomes from published investigations on the gender disparity in prognosis of bladder malignancy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Bladder malignancy is further frequently noted among males, while prognosis is generally worse among females. 13 In this study males were found in the majority 51(61.4%) and females were 32(38.6%), which is similar to the study of Türk H et al, 13 which reported that out of five hundred sixty-nine patients, 497 (87.30%) cases were males and 72 (12.70%) were females. In recent times, many reviews have summarized and interpreted outcomes from published investigations on the gender disparity in prognosis of bladder malignancy.…”
Section: Discussionsupporting
confidence: 89%
“…In this series no significant variance was found in age groups in terms of grading of malignancy, while other studies reported that old age is significantly correlated with high grade urothelial malignancy. 13,20,21 This difference may be because age range was lower in our study in contrast to other studies.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation